Winthrop Alchemical Manuscript
Two volumes concerning the Winthrop Alchemical
Photocopy of original in the Massachusetts Historical Society (Boston).
Massachusetts: Massachusetts Historical Society, Boston
Collection material in English.
Keywords: Winthrop, John, -- 1606-1676.; Alchemy